Pengaruh Konsumsi Jus Nanas Terhadap Kadar Asam Urat Pada Wanita Menopause - Ikhwani Ikhwani; Supriyatin Supriyatin; Misika Alam (Jurnal Sains dan Kesehatan, 2021)
Abstract. Gout often attacks people over the age of 30, this is because at that age the declining esterogenous levels can cause uric acid levels in the blood to increase. High uric acid levels can be overcome with a variety of treatments including nonpharmacological treatment in the form of giving pineapple juice. Prevention that can be done to keep uric acid levels normal is by limiting purine foods, choosing low-purine foods, avoiding taking drugs, and taking vitamin C supplements including consuming pineapple juice. The purpose of this study was to determine uric acid levels before and after giving pineapple juice and to determine the difference in results before and after giving pineapple juice on uric acid levels in menopausal women. The research method was pre experiment and the method of examining uric acid levels using the POCT method. The population in the study were 25 menopausal women aged 45-55 years in RW 3 Kaliwadas Village, Cirebon Regency. The sample in the study was 22 menopausal women, with the sampling technique using purposive sampling. Data from the examination of uric acid levels before and after the administration of pineapple juice obtained the results of 21 samples that experienced a decrease (95.45%) and 1 sample that experienced an increase (4.45%) with an average uric acid level before 5.6 mg/dL with the highest level of 8.4 mg/dL and the lowest level of 4.7 mg/dL and the average after 5.3 mg/dL with the highest level of 8.4 mg/dL and the lowest level of 3.7 mg/dL. The research data were analyzed using a normality test and paired sample T-test obtained Sig. (2-tailed) 0.000 <0.005. based on this study it can be concluded that there is an influence on uric acid levels before and after being given pineapple juice.